PENGEMBANGAN PEMROSESAN FOTOGRAMETRI DIGITAL FOTO UDARA FORMAT KECIL UNTUK PENYEDIAAN DATA SPASIAL - , Harintaka, ST.,MT. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Small Format Aerial Photography (SFAP) has various advantages, such as: low operational cost, easy-to-obtain equipment, and rapid processing for data acquisition. However, SFAP also has disadvantages in relation to geometric accuracy and stability of camera lens, instability of aircraft movement during exposure, and quality of position accuracy that has yet to be proven. SFAP has been utilized to identify thematic information of earthâs surface for a reasonably long time. Accordingly, it is potential that SFAP is to be used for spatial data provision by minimizing its disadvantages. This research is aimed at developing procedures for digital processing of SFAP for spatial data provision. The objectives of this research are to identify and model the Interior Orientation Parameter (IOP) of non-metric camera, to automatically and interactively extract vertical position, and to study the quality of the resulted spatial data in accordance to several spatial data specification standard. This research was carried out in six steps. The first step is network design, installation, survey and data processing of ground control points. The second step is design and perform calibration of SFAF system to define IOP value and its stability. Thirdly, aerial photography was carried out using ultra-light aircraft. The fourth step is single and multi-photo processing. Single-photo processing includes interior orientation and systematic error correction. Multi-photo processing includes aerial triangulation (AT) adjustment, standard AT, and AT with Additional Parameters (AP). The fifth step is automatic and interactive extraction of 3D position. The final or sixth step is performing study on the quality of spatial information. Study results show that (1) to overcome IOP instability, in-flight camera calibration is required